MEDIA PEMBELAJARAN ANIMASI INTERAKTIF MENGENAL KEBUDAYAAN NUSANTARA - Handini Widyastuti; Sahwa Wulanuari (Universitas Sahid Surakarta, 2020)
Basically, animation is a form of entertainment, and by making learning media can make children, especially elementary school students, be more happy in learning. Learning methods used in primary schools still use lecture or face-to-face methods to students, so it is necessary to add more interesting learning media. In the teaching process, teachers only use the media as a guide for teaching, as a result students find it difficult to know clearly about the culture of the archipelago. In this study the authors took research material from the results of observations and interviews with several students in elementary schools, teachers and related parties. For this reason, the authors make the Interactive Animation Program to Know the Archipelago Culture a solution for elementary school students in learning the types of archipelago culture and to facilitate and improve efficiency in the learning process.